Participation and Alternative Economic Practice: Discourses, Identities and Imaginaries of Change - Pascual, Henar; Guerra, Juan Carlos (PARTECIPAZIONE E CONFLITTO, 2021)
In the context of economies referred to as diverse or different, Alternative Economic Practices (AEP) are actions that, alternative to capitalism in varying degrees, aim to fulfil people's basic needs. The Great Recession of 2008 gives a new incentive to their theoretical and empirical analysis as a result of the new meaning given to alternative economic and political spaces, particularly in an area hit hard by the crisis – Southern Europe. This paper examines an aspect hardly represented in academic literature: the profile of the social basis of alterna-tive economic practices and its operational significance. By means of the frameworks provided by institutional economic geography and contributions made by the theo-ry on urban social movements as well as social mobilisation, it explores the characteristics of the social basis of Spanish AEP using that which prior studies highlighted from the profile of the participants in Greek practices as a point of comparison and reference. We suggest that the contextual conditions determine the attributes of the key actors and the strategies to challenge the existing social institutions and structures and mobilise the social forces to support collective projects that contradict the dominant relations. The result is that of nominally identi-cal AEP, belonging to a common alternative repertoire yet composed of social bases with clearly distinct pro-files. This means that both are built upon different values, discourses, motivations and identities, leading to their varied geographical significance and potential to transform.